FACTORS RELATING TO PUBLIC MOTHER’S VISITS IN THE WORKING AREA OF THE PUSKESMAS IN THE VILLAGE OF HAMPARAN PERAK PERAK - Sinaga, Esra E; Siti Nurmawan Sinaga; Dessy Ratna Sari; Minta Punguan Simbolon; Rauni Gultom; Nisa Arisma; Indra Septiadi Manurung (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
One of the successes of the postpartum period is to prevent maternal mortality during the postpartum period. Health services for postpartum mothers are needed because the 2 month period after giving birth to the mother’s physical condition has not fully recovered, so she is vulnerable to various related infectious diseases and can pose a risk of maternal death. WHO estimates that around 10.7 million women worldwide die from childbirth and 25-50% of the causes are health problems, childbirth and childbirth. This study aims to determine the relationship between age, occupation, education, pregnancy distance, and parity on postpartum visits in the Samata Gowa Health Center work area in 2019-2020. This type of research is an analytical study with a cross-sectional study design. The population of this study were all postpartum mothers who were recorded visiting the Samata Gowa Public Health Center register book in the time span starting from January 2019 to October 2020, namely 489 people. The sampling technique used was simple random sampling with a total sample of 141 postpartum mothers. Data analysis used univariate and bivariate analysis. The results showed that as many as 41.8% of respondents who were incomplete made postnatal visits and 58.2% who were complete made postnatal visits. There is no relationship between age and value (p = 0.602), work with value (p = 1,000), education with value (p = 0.955), pregnancy distance with value (p = 0.353) and there is a relationship between parity (p = 0.038) with postpartum visits at Samata Gowa Health Center. Conclusion: In this study, it can be seen that there is a relationship between parity and postpartum visits. Meanwhile, age, occupation, education and pregnancy distance showed that there was no relationship with postpartum visits. This study suggests increasing awareness and emphasizing counseling for postpartum mothers who think that they will not be at risk / low risk during the postpartum period and it is hoped that mothers can limit parity in order to maximize the implementation of routine postpartum visits to anticipate complications during childbirth Bibliography : 42 (2010-2020)